1983
DOI: 10.1093/jaoac/66.3.610
|View full text |Cite
|
Sign up to set email alerts
|

Hot Leaching of Ceramic and Enameled Cookware: Collaborative Study

Abstract: A hot leach method published by the World Health Organization for determining Pb and Cd in ceramic and enameled ware was collaboratively studied in 14 laboratories. The method consisted of heating a solution of 4% acetic acid at the boil for 2 h in 6 samples of specially glazed ceramic ware and 6 samples of special enameled ware. The acid was allowed to cool and stand in contact with the ware for an additional 22 h. At the end of the 2 h heating period and again at the end of the 24 h period, the leach solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For each pH, before attending the plateau, a linear relationship between the contact time and the amount of released Pb was found. The same relationship was found by Gould et al [26]. For each pH, the slope of the fitted linear model was calculated.…”
Section: Resultsmentioning
confidence: 64%
“…For each pH, before attending the plateau, a linear relationship between the contact time and the amount of released Pb was found. The same relationship was found by Gould et al [26]. For each pH, the slope of the fitted linear model was calculated.…”
Section: Resultsmentioning
confidence: 64%
“…(Tassi et al, 2014) studied the migration of Cu, Cr, Cd, Al, Fe, Mn, Ni, and Pb from carbon steel cylinders to food gases and stored up to 50 day, the migration was lower for metals. (Quintaes et al, 2006) (Gould et al, 1983). Raw faba bean mean : faba bean before cooking.…”
Section: Results and Disscutionmentioning
confidence: 99%
“…The leaching of metals induced by acetic acid, which was used to simulate the prolonged use of the containers, shows that metal leaching increases with increased use of the containers. This method to establish the amount of metals that are leached by acetic acid has been well utilized by several authors [ 37 , 41 44 ], who have shown that clay containers from Mexico, Italy, and other countries have high concentrations of heavy metals, mainly lead, surpassing the limits allowed by the FDA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the lowest levels of leached cadmium and lead were found in Tulancingo, these levels remain higher than those reported by Gould et al ., in 1983 [ 41 ]. However, there are works in which even greater leaching of both metals have been reported [ 37 , 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation